7-Amino-3, 4-dihydro-1H-quinolin-2-one, a compound similar to the substituted coumarins, inhibits α-carbonic anhydrases without hydrolysis of the lactam ring. (October 2015) - Vullo, Daniela; Isik, Semra; Bozdag, Murat; Carta, Fabrizio; Supuran, Claudiu T.
Abstract 7-Amino-3, 4-dihydro-1H-quinolin-2-one, a compound structurally similar to coumarins, recently discovered class of inhibitors of the α-carbonic anhydrases (CAs, EC 4.2.1.1) was investigated for its interaction with all human (h) CA isoforms, hCA I-XIV. The compound was not an inhibitor of the cytosolic, widespread isoform hCA II (KI > 10 µM), was a weak inhibitor of hCA I, III, IV, VA, VI and XIII (KIs in the range of 0.90–9.5 µM) but effectively inhibited the cytosolic isoform hCA VII (KI of 480 nM) as well as the transmembrane isoforms hCA IX, XII and XIV (KIs in the range of 16.1–510 nM). Against many CA isoforms this lactam was a better inhibitor compared to the structurally similar 4-methyl-7-aminocoumarin, but unlike this compound, the lactam ring was not hydrolyzed and the inhibition was due to the intact bicyclic amino-quinolinone scaffold. Bicyclic lactams strucurally related to coumarins are thus a new class of CA inhibitors possessing however a distinct inhibition mechanism compared to the coumarins which undergo a hydrolysis of their lactone ring for generating the enzyme inhibitory species.